Construction and validation of a Survey to measure perceptions of snakes. Issue 2 (3rd April 2019) - Horsley, Sarah; Green, Gary T.
ABSTRACT: We developed a survey to measure education program participants' perceptions of snakes. This survey was created from new and existing items, pilot tested, and edited to final items representing attitude and behavior dimensions. We implemented the final survey as pre- and posttest among participants of snake education programs in Athens, Georgia and national citizen science programs. A Principal Component Analysis of posttest survey data ( N = 259) revealed six dimensions (Moralistic-Ecologisitic, Negativistic, Utilitarian-Ecologistic, Scientistic, Contact Willingness, and Protection Advocacy). Factor loadings and reliability coefficients indicated the survey measured appropriate dimensions and was a valid and reliable instrument assessing education participants' snake perceptions.